Measurement Of Bradykinin-Induced Venous Dilation By Ultrasound And Correlation With Heart Rate, Arterial And Venous Pressure And Endothelial Damage - Stewart, G J; Schaub, R G; Cartee, R E (Thrombosis and Haemostasis, 1981)
This study was done to correlate known cardiovascular responses to bradykinin (increased heart rate, lowered arterial blood pressure) with recently demonstrated endothelial damage and proposed venous dilation. Healthy dogs of mixed breed were used. Blood pressures and heart rate were monitored and recorded on a Narco physiograph. The diameter of a jugular vein was monitored with an ADR ultrasound machine using a 10 MHz probe with linear array of crystals and recorded on polaroid prints. Jugular veins and carotid arteries were removed and prepared for scanning electron microscopy after removal of blood and partial in situ fixation by whole body perfusion. The response of arterial pressure was dose dependent with no change at 6 ug/min, variable drop at 12 ug/min and 22-40% drop at 60 ug/min and above. Venous pressure increased in 1 dog but was unchanged in 4 others. The increase of heart rate paralled the drop in arterial blood pressure. The diameter of a jugular vein increased in 3 of 3 monitored dogs by 25, 33, 50% of baseline diameter (average increase 36%) with high (300 ug/min) bradykinin. Endothelial damage (microtears) occurred around 70-80% of branches, at some valves and on the main vessel occassionally. The tears were infiltrated with leukocytes and some red cells and platelets indicating that tearing occurred while blood was still circulating, i.e. before dissection for removal of vessels. Carotid arteries showed no tears. Dilation of arteries would be limited by their elastic layers (missing in veins). These observations show that venous dilation and endothelial tearing around side branches are part of the cardiovascular response to blood born bradykinin. They also show that venous dilation can be measured by ultrasound.